2015
DOI: 10.1186/s40068-015-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium leguminosarum bv. viciae sp. inoculation improves the agronomic efficiency of N of common bean (Phaseolus vulgaris L.)

Abstract: Background: Due to common bean derives lower nitrogen (N) from symbiotic N 2 -fixation, it requires N either from inorganic fertilizer or soil N. Field experiments were conducted at four locations to evaluate the effect of Rhizobium leguminosarum bv. phaseoli inoculation on agronomic efficiency of N of common bean var. Dursitu major growing areas of eastern Ethiopia. ) and two inoculation treatments (uninoculated and inoculated) were factorially combined and laid out in randomized completely block design, repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
4
7
0
Order By: Relevance
“…Brockwell et al [85] confirmed that nodulation has been decreased at high N rates irrespective of levels of inoculation. Similar findings have been signified in chickpea [86] and beans [87]. Furthermore, various study results revealed the reduction in nodule formation (nodule number and dry weight) with increased application rates of inorganic N to inoculated chickpea [82,83].…”
Section: Effect Of Rhizobium Inoculation On Nodulation Growth and Yield Performance Of Chickpeasupporting
confidence: 82%
“…Brockwell et al [85] confirmed that nodulation has been decreased at high N rates irrespective of levels of inoculation. Similar findings have been signified in chickpea [86] and beans [87]. Furthermore, various study results revealed the reduction in nodule formation (nodule number and dry weight) with increased application rates of inorganic N to inoculated chickpea [82,83].…”
Section: Effect Of Rhizobium Inoculation On Nodulation Growth and Yield Performance Of Chickpeasupporting
confidence: 82%
“…These results are similar to another report [22] that inoculation alone increased seed yield of lentil by 135%. Our results are also in line with a recent study [26] that indicates inoculation with elite indigenous isolates of common bean nodulating rhizobia improved the use efficiency of N and reduced the need of exogenous N application to get maximum yield in eastern Ethiopia. Experiments conducted in Western Canada failed to demonstrate any yield advantage from applying N fertilizer to lentil relative to the current practice of relying on N 2 fixation.…”
Section: Grain Yield and Yield Componentssupporting
confidence: 81%
“…Hence, soybean requires a lower N rate as a starter during inoculation than a chickpea. An increase in grain yield of common bean with increasing rates of N application in the presence of Rhizobium inoculation was also previously observed by Argaw and Akuma (2015) under field conditions in Ethiopia. However, Da Silva et al (1993) also found that both foliar and soil N application methods inhibited nodulation at high N rates and did not significantly increase common bean yield compared with low N rate (10 kg N ha −1 ).…”
Section: Discussionsupporting
confidence: 75%